Plasticity-based training: building the ultimate learning organization. Issue 6 (6th November 2017) - Merzenich, Michael
Abstract : Purpose: This paper aims to introduce talent development professionals to the most recent breakthroughs in the science of neuroplasticity and how those breakthroughs directly apply to building better brains and a true learning organization. Brain plasticity is the ability of the brain to change chemically, physically, and functionally based on sensory and other inputs. Design/methodology/approach: Viewpoint based on literature review and author's own neuroscientific research over the past 30 years. Findings: Gains can be made on standard measures of processing speed, attention, memory, and executive function and those changes generalize to standard measures of mood and affect the real-world activities. Benefits, seen in experiments over the past few years for peak sports performance, are now being applied in the workplace Practical implications: It is hard to think of any job, where a faster and more accurate brain would not help. Originality/value: Many learning and development professionals are not yet aware of the health and performance benefits of plasticity-based training. This paper provides summarized evidence of its efficacy for individuals and organizations.